Design of a collector for sampling volcanic ash using unmanned aerial systems. (March 2023) - MacLeod, James; Wood, Kieran; Rendall, Thomas; Watson, Matthew; Allen, Christian; Reader, Madeleine; Lucas, Josh; Richardson, Thomas
Abstract: Volcanic ash is an aerial hazard to both aircraft and local populations, hence efforts to monitor and quantify its presence are underway in many regions, both to protect airspace users and as a modeling tool for volcanology. One direct approach is to acquire in-situ ash samples using an unmanned vehicle, but this introduces possible bias in the samples due to the collector system, especially across the full range of ash particle sizes. This work explores an open impact type design of miniaturized airborne ash collector and quantifies the influence of the collector geometry on the measured particle size distribution. Results indicate that the distribution of sizes measured can be strongly influenced by the collector design, owing to the influence of the geometry on the aerodynamics and hence the particle trajectories. Comparisons to experimental flight data illustrate that the simulations provide a representative model, and that a design featuring a bluff fore-body separates and mixes the flow, making it more capable of capturing small particles than a planar surface in isolation. Highlights: Presence of an upstream disruptor improves sample of micron-scale particles. Stub face impacts have qualitative agreement with flight gathered samples. Collection efficiency recommended as calibration metric for flight samples. Vortex entrainment of particles produces complex trajectories across stub face. Improved understanding of impact locations across stub faces for sampling.